A experiência dos planos diretores no estado do Amapá: análise das dimensões institucionais, econômicas e ambientais - José Alberto Tostes (Confins)
The article compares the institutional, economic, and environmental perspectives dimensions of six different Amapá master plans produced between 2004 and 2020. Those plans are important marks to help understand the usage of urban territory. The chosen methodology is drawn from officially published documents that show Amapá reality. The theoretical discussion relies on the vision of urban planning. As relevant conclusions, the plans contributed to the advancement of the entire territorial space of the municipality, although the potential that could leverage urban and rural development was restricted by the absence of planning and management strategies.